2018
DOI: 10.1016/j.jbo.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to alendronate is associated with a lower risk of bone metastases in osteoporotic women with early breast cancer

Abstract: BackgroundBisphosphonate (BP) treatment to prevent bone loss in breast cancer patients is already well established. However, data on the association between oral BP exposure before cancer diagnosis and disease outcomes in patients with early breast cancer are still scarce. Limited information is available on alendronate, the most common oral agent for the treatment of post-menopausal osteoporosis, regarding the association with bone metastases.AimTo examine the association between oral bisphosphonate exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…(16) However, similar effects are seen in non-neoplastic cells, so this probably represents a nonspecific toxicity from high doses of these drugs. (24) The UK General Practice Database showed reduced risk of all cancers, and of breast and colorectal cancers specifically, in bisphosphonate users, (25) and a nationwide Danish database suggested protection against colon cancer with alendronate use. (17,18) Third, observational studies have reported that oral bisphosphonate use is associated with fewer first breast cancers (19)(20)(21) ; reduced risk of contralateral breast cancer (OR = 0.4) (22) ; reduced risk of a combined endpoint of recurrence, second primary breast cancer, and breast cancer mortality (23) ; and reduced risk of skeletal metastases in early breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) However, similar effects are seen in non-neoplastic cells, so this probably represents a nonspecific toxicity from high doses of these drugs. (24) The UK General Practice Database showed reduced risk of all cancers, and of breast and colorectal cancers specifically, in bisphosphonate users, (25) and a nationwide Danish database suggested protection against colon cancer with alendronate use. (17,18) Third, observational studies have reported that oral bisphosphonate use is associated with fewer first breast cancers (19)(20)(21) ; reduced risk of contralateral breast cancer (OR = 0.4) (22) ; reduced risk of a combined endpoint of recurrence, second primary breast cancer, and breast cancer mortality (23) ; and reduced risk of skeletal metastases in early breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) Third, observational studies have reported that oral bisphosphonate use is associated with fewer first breast cancers (19)(20)(21) ; reduced risk of contralateral breast cancer (OR = 0.4) (22) ; reduced risk of a combined endpoint of recurrence, second primary breast cancer, and breast cancer mortality (23) ; and reduced risk of skeletal metastases in early breast cancer. (24) The UK General Practice Database showed reduced risk of all cancers, and of breast and colorectal cancers specifically, in bisphosphonate users, (25) and a nationwide Danish database suggested protection against colon cancer with alendronate use. (26) A meta-analysis of observational studies of colon cancer also found a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, the effect of these inhibitors of bone resorption are promising. For example, in patients with early breast cancer adjuvant therapy with bisphosphonates was shown to increase survival benefit and reduce bone metastatic burden [111][112][113]. Similarly, treatment with denosumab was found to increase bone metastasis-free survival in prostate cancer patients [114,115].…”
Section: Accepted Articlementioning
confidence: 99%
“…The EBCTCG meta-analysis on adjuvant use of bisphosphonates concluded there was insufficient evidence for the use of alendronate and risedronate in the adjuvant setting of breast cancer [7]. Nevertheless, non-prospective trials suggest this relationship also exists for these oral bisphosphonates [22,23]. Hopefully, future prospective trials will clarify this matter.…”
Section: Discussionmentioning
confidence: 99%